Fabrication and characterisation of nitrogen-doped diamond microtools. (23rd January 2008) - Jackson, Mark J.
Chemical vapour deposited diamond films have many industrial applications but are assuming increasing importance in the area of microfabrication, most notably in the development of diamond-coated microtools. For these applications the control of structure and morphology is of critical importance. The crystallite size, orientation, surface roughness and the degree of sp³ character have a profound effect on the machining properties of the films deposited. In this paper experimental results are presented on the effects of nitrogen doping on the surface morphology, crystallite size and wear of microtools. The sp³ character optimises at 200 ppm of nitrogen and above this value the surface becomes much smoother and crystal sizes decrease considerably. Fracture induced wear of the diamond grain is the most important mechanism of material removal from a microgrinding tool during the grinding process. Fracture occurs as a consequence of tensile stresses induced into diamond grains by grinding forces to which they are subjected. The relationship between the wear of diamond-coated grinding tools, component grinding forces and induced stresses in the model diamond grains is described in detail. A significant correlation is found between the maximum value of tensile stress induced in the diamond grain and the appropriate wheel-wear parameter (grinding ratio) machining a selection of engineering steels and cast iron materials. It is concluded that the magnitude of tensile stresses induced in the diamond grain by grinding forces at the rake face is the best indicator of tool wear during the grinding process.